Studi Kasus Pengaruh Pengangguran Dan Kemiskinan Terhadap Pertumbuhan Ekonomi Jawa Barat Tahun 2012-2021 - Aliya Putri, Cantika Sindy; Rahmadhani, Muntiara Putri; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
To measure macroeconomic performance can be seen from economic indicators, one of which is unemployment. If the number of unemployed is high, it means that most people do not have income to support themselves, which causes a decrease in demand. In West JavaÂ  the unemployment rate is quite low. This study analyzes the effect of economic growth in West Java in 2012-2021. The dependent variable is economic growth in West JavaÂ  and the independent variable is unemployment and poverty in West Java . The Data used is time series data for 10 years (2012-2021). The results showed that the variable unemployment resulted in significant positive to economic growth in West Java. Meanwhile, the poverty variable showed positive and insignificant results on economic growth in West Java . This is because employment has increased the largest contribution to employment.